Electrophysiological and Cognitive Changes in Hard Coal Miners Associated with Working Underground - Çelik, Samet; Yildirim, Ebru; Guntekin, Bahar; Çelik, Samet (Sage Publications Inc, 2024)
Miners working underground face some risk factors that affect the nervous system-such as high noise, dark environment, chronic stress, and exposure to toxic gases. However, it is not known whether these risk factors affect the cognition of miners. In this study, the cognitive changes of miners were examined through event-related oscillations via electroencephalogram (EEG). Twenty underground miners and control groups, equal to each other in age, education level, and working duration, participated in this study. Neuropsychological tests were applied to all participants to examine their cognitive characteristics. Then, 20-channel EEG was recorded for electrophysiological changes during visual oddball paradigm. Event-related power spectrum and phase locking were analyzed in delta (0.5-3.5), theta (4-7), and alpha (8-13 Hz) frequency bands. It was determined that the delta responses that emerged during the target stimulus differed between the two groups in terms of phase locking (p < 0.05). Considering event-related alpha responses, a statistical difference was found regarding power spectrum and phase locking (p < 0.05). Moreover, the alpha power spectrum in the miners was found to be negatively statistically correlated with working duration (p < 0.05). This study determined that the event-related electrophysiological responses of the miners were negatively affected depending on the working conditions. In addition, neuropsychological assessment determined miners had deficiencies in learning and memory skills and many other cognitive functions such as attention, behavioral inhibition, and visual perception.
Keywords: Event-Related Oscillations; Worker Health And Safety; Occupational Health; Underground Miners; Cognition